2018
DOI: 10.3390/su10072120
|View full text |Cite
|
Sign up to set email alerts
|

Is Land Fragmentation Facilitating or Obstructing Adoption of Climate Adaptation Measures in Ethiopia?

Abstract: Land fragmentation is high and increasing in the Gamo Highlands of southwest Ethiopia. We postulate that this substantial land fragmentation is obstructing the adoption of sustainable land management practices as climate adaptation measures. To explore this, a mixed method study was conducted with emphasis on a multivariate probit model. The results indicate that farmers adapt to climate change and variability they perceive. According to the probit model, there is no clear answer to the question whether land f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 57 publications
4
20
0
9
Order By: Relevance
“…Moreover, farmlands closer to the homesteads can be better monitored and taken care of, enabling more frequent supervision of the implemented conservation measures [2]. Consistently, Pender and Gebremedhin [58], Abebe and Sewnet [59] and Cholo, et al [60] reported that farmers give more attention to farm plots closer to homestead areas than distant farm plots. This also enables farmers (farm owners) and/or other neighboring farmers to observe the effects of implemented stone bunds, suggesting that visible effects are crucial in terms of triggering spontaneous adoption and implementation of technologies.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, farmlands closer to the homesteads can be better monitored and taken care of, enabling more frequent supervision of the implemented conservation measures [2]. Consistently, Pender and Gebremedhin [58], Abebe and Sewnet [59] and Cholo, et al [60] reported that farmers give more attention to farm plots closer to homestead areas than distant farm plots. This also enables farmers (farm owners) and/or other neighboring farmers to observe the effects of implemented stone bunds, suggesting that visible effects are crucial in terms of triggering spontaneous adoption and implementation of technologies.…”
Section: Discussionmentioning
confidence: 93%
“… Policy A few papers discussed agricultural policies related to seed, arguing that policies should enable the seed sector to provide suitable varieties and aim to increase the availability of funds for seed distribution research and access to improved seed, and one paper indicated that government policies restrict farmers options for obtaining their preferred seed 48 – 50 . Experience One paper indicated that farmers’ experience had a positive effect on adoption of new seed, whereas another indicated the opposite 9 , 51 . Seed or variety attributes Four papers reported on concerns related to the attributes of the hybrid seed varieties and their adaptation to the environment, suitability for storage, flour to grain ratio, and other processing issues 52 54 .…”
Section: Resultsmentioning
confidence: 99%
“…One paper indicated that farmers' experience had a positive effect on adoption of new seed, whereas another indicated the opposite 9,51 .…”
Section: Experiencementioning
confidence: 99%
“…Moreover, farmlands closer to the homesteads can be better monitored and taken care of, enabling more frequent supervision of the implemented conservation measures (Bekele & Drake, 2003). Consistently, Pender & Gebremedhin (2008), Abebe & Sewnet (2014) and Cholo et al (2018) reported that farmers give more attention to farm plots closer to homestead areas than distant farm plots. This also enables farmers (farm owners) and/or other neighboring farmers to observe the effects of implemented stone bunds, suggesting that visible effects are crucial in terms of triggering spontaneous adoption and implementation of technologies.…”
Section: Discussionmentioning
confidence: 81%